METABOLIC BASIS OF PREVENTION OXALATE NEPHROPATHY AND URINARY SYSTEM INFECTION IN CHILDREN (American Journal of Interdisciplinary Research and Development, 2023)
All over the world diseases of the urinary system are becoming one of the urgent problems. According to the World Health Organization, complications of kidney disease are of great importance for the public health system in all countries, depending on the place of residence, lifestyle, gender, age, nutritional status, under the influence of environmental factors, there is a risk to the lives of children and adults. In this regard, the problem of early diagnosis, the appointment of adequate dietary and drug therapy is relevant.